Kontestasi Pemaknaan Kepemimpinan Publik di PILGUB DKI: Perspektif Relasi Kuasa - Zauhair Al Fawwaz, Fajriz; Musthafa, Adib Khairil (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2024)
This article explains about the hegemony of MUI related to the blasphemy case in the 2017 DKI Pilgub which is based on surah al-Maidah verse 51, there are various opinions that give birth to community polarization. Therefore, this article will answer the question of how the relevant meaning today of the word